Enhancing running injury prevention strategies with real-time biofeedback: A systematic review and meta-analysis - Shen, W.; Yu, Y.; Frias Bocanegra, J.; Wheeler, P. C.; Fong, D. T. (Journal of Sports Sciences, 2024)
The number of runners and the incidence of running-related injuries (RRIs) are on the rise. Real-time biofeedback gait retraining offers a promising approach to RRIs prevention. However, due to the diversity in study designs and reported outcomes, there remains uncertainty regarding the efficacy of different forms of feedback on running gait biomechanics. Three databases: MEDLINE, PUBMED, and SPORTDiscus were searched to identify relevant studies published up to March 2024, yielding 4646 articles for review. The quality of the included studies was assessed using the Downs and Black Quality checklist. Primary outcomes, including Peak Tibial Acceleration (PTA), Vertical Average Loading Rate (VALR), and Vertical Instantaneous Loading Rate (VILR), were analysed through meta-analysis. 24 studies met the inclusion criteria and were analysed in this review.17 used visual biofeedback (VB) while 14 chose auditory biofeedback (AB). The meta-analysis revealed a reduction in loading variables both immediately following the intervention and after extended training, with both visual and auditory feedback. Notably, the decrease in loading variables was more pronounced post-training and VB proved to be more effective than AB. Real-time biofeedback interventions are effective in lowering loading variables associated with RRIs. The impact is more substantial with sustained training, and VB outperforms AB in terms of effectiveness.